Optical Parameters of Atomically Heterogeneous Systems Created by Plasma Based Low Energy Ion Beams: Wavelength Dependence and Effective Medium Model - Singh, Krishn Pal; Bhattacharjee , Sudeep (Frontiers in Physics, 2021)
The present article presents the irradiation effects of low energy ( 0.5 keV) inert gaseous Argon ion beams on optical constants (real (n) and imaginary (k) parts of the refractive index), dielectric constants, skin depth, and optical conductivity of copper (Cu), silver (Ag), and aluminum (Al) metallic thin films (MTF). The optical constants of pristine MTF are obtained by employing the universal Kramers-Kronig (KK) technique. The reflectivity of pristine MTF measured using UV-VIS-NIR spectrophotometry is used as an input parameter in the KK technique to determine the optical constants as a function of energy (or wavelength (lambda)) of incident light ranging between 1-4.96 eV (or 250-1200 nm). For the irradiated MTF, the optical constants including the skin depth (delta = lambda/ 2 pi k), optical conductivity (sigma = nkc/ lambda), and dielectric constants (epsilon_1 = n^2 - k^2 and